Physicochemical Characteristics and Levels of Cu, Fe, Pb, Mn and Zn in Sediments of Agbarho River, Delta State, Nigeria - O. O. Okome; D. Okoro (Journal of Applied Sciences and Environmental Management)
Sediment qualities assessment to ascertain the impact of anthropogenic activities such as dredging, waste disposal, and abattoir effluent on the sediments of a river is very vital. Hence, the objective of this paper was to evaluate the physicochemical Characteristics and Levels of Cu, Fe, Pb, Mn, and Zn in the Sediments of Agbarho River, Delta State, Nigeria using appropriate standard methods. The ranges of results obtained were; pH = 4.0 – 5.3, EC = 10.00 – 246.00μS/cm, OC = 0.36 – 62.72 LOI, N = 0.006 – 0.590 %, Clay = 6 – 14 %, Sand = 76 – 92 %, Silt = 2 – 11 %, Cu = 2.33 – 5.19 mg/kg, Zn = 4.71 – 81.78 mg/kg, Fe = 57.18 – 385.45 mg/kg, Mn = 1.60 – 42.43 mg/kg, Pb = 0.19 – 0.63 mg/kg. Assessment of heavy metals pollution, using pollution indices revealed that the contamination factor was low compared to NUPRC and other standard guidelines/values. These results obtained showed that there was no contamination in the study area.